PSYCHOLOGICAL CAPITAL ОF PROJECT MANAGER - Ermolaeva, M.V.; Lubovsky, D.V. (Modern Psychology, 2019)
This article analyzes the possibility of using approaches and theoretical models developed in modern positive psychology to study the psychological capital of project managers. The analysis of modern research has shown the applicability of the approach to the study of prosperity and the five-factor model "PERMA", proposed by M. Seligman, to the study of the psychological capital of project managers. The means used by successful project managers to form positive relationships in the group, involvement, positive emotions are analyzed. The article discusses the possibility of applying the findings in the preparation of project managers in the conditions of widespread project methods in modern Russian higher education.